Penegakan Hukum Pidana Terhadap Penyelundupan Hewan Satwa - I Gusti Ngurah Made Suradnya; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2021)
Animals that must be protected where it gets protected by the government. Which in this case makes the public should not take actions that are not following the rules set by the government in this case against protected animals. If seen in article 1 number 1 law No. 5 of 1990 on Conservation of Natural Resources mentioned that individual animals are animals that grow and live on land, air, and water that have different wild properties, even those maintained by humans or live in the wild. The formulation in this study is as follows how is the legal regulation of animal smuggling and how are criminal sanctions against animal smuggling. The method used is a method of normative legal research. It is expected that the government and the people of Indonesia, in particular, to be willing to participate in protecting and eradicating people in terms of hunting protected wild animals, where it aims to keep rare animals around us sustainable